Capturing Emotional Foot Print of Speakers at Convocation Addresses of Select Management Institutions in India - Ramesh, Avadhanam; Nalluri, Padmaja (Prabandhan: Indian Journal of Management, 2019)
A convocation is a solemn occasion for the academic institutions, as it indicates the culmination of gallant efforts by students and faculty, etc. A convocation address by the chief guest leaves an indelible impression on the minds of graduating students who are raring to go and prove their mettle in the industry. An emotional footprint like a carbon footprint is equally important, affecting the working environment of the organization and the people. The present research paper attempted to capture the emotional footprint of the speeches at the convocation addresses of the year 2017 at world-class management institutions of India namely IIM Ahmedabad and IIM Bangalore. The paper also examined the emotional footprint of the speeches using 4B’s framework of Saul Levine and the degree of persuasion in speeches through the lens of Aristotle’s rhetoric. The study employed text analytics to see the pattern of the speeches by observing the number of words, sentences, characters, readability of the text, and sentiment analysis for identifying various shades of emotions, and data visualization tools were used to capture the salient aspects of the convocation addresses. The study found that the convocation speeches had all the dimensions of emotional footprint namely the four B’s : being, belonging, believing, and benevolence. The study found that the overall sentiment of both the speeches was positive, and aroused emotions of happiness, liking, and calmness. Aristotle’s rhetoric reveals that both the speakers used all three types of appeals: ethos, logical, and emotional aspects in their speeches, which left a positive emotional footprint on the audience.